The use of methylphenidate hydrochloride and its influencing factors in the lives of young Medical students (Research, Society and Development, 2022)
Introduction: Methylphenidate Hydrochloride is a mechanism used by young medical students to improve performance and academic prominence, since they are subjected to extensive workloads, excessive charges and competition for success. Objective: Research the conditions that influence the use of Methylphenidate Hydrochloride, describe the motivational factors, detail the academic profile and acquisition by other psychostimulants, among students of the first and eighth semesters of the Medicine course in a private institution in Palmas-TO. Methods: This is a prospective observational epidemiological study with a descriptive and analytical focus; presenting a cross-sectional approach to the prevalence indicator of medical students from the first to the eighth periods who agreed to participate in the research, by signing the Free and Informed Consent Form. Data collection took place through the application of a questionnaire, with the theme: “The use of Ritalin and its influence on the lives of medical students at ITPAC Palmas”. Results: 190 people participated, of which 44.7% know the mechanism of action of Methylphenidate Hydrochloride and 33.2% have already used the drug, showing an increase of 32.6% in concentration during activities and 22, 1% reported having side effects. Furthermore, 42.1% of the students have already used another psychostimulant drug or stimulants in general, of which 48.9% of the total population of research participants were without a prescription. Conclusions: It is observed that the use of Ritalin is relatively low among medical students at ITPAC Palmas, since most respondents already know the drug. However, there is a significant increase in other drugs and stimulants in general, seeking the same objective, and it is notable that both had a worrying number in indiscriminate use.